Peripheral Nerve Blockade for Medial Patellofemoral Ligament Reconstruction in Pediatric Patients: The Addition of a Proximal Single-Injection Sciatic Nerve Block Provides Improved Analgesia - Halpern L; Kogan CJ; Arnzen G (Local and Regional Anesthesia, 2022)
Lloyd Halpern,1 Clark J Kogan,2 Grady Arnzen3 1Department of Anesthesia, Shriners Children’s Hospital, Spokane, WA, USA; 2Department of Interdisciplinary Statistical Education and Research, Washington State University, Spokane, WA, USA; 3Creighton University School of Medicine, Omaha, NE, USACorrespondence: Lloyd Halpern, Department of Anesthesia, Shriners Children’s Hospital, 911 W. 5th Ave, Spokane, WA, 99204, USA, Email lhalpern@shrinenet.orgPurpose: We tested the hypothesis that the addition of a single-injection proximal sciatic nerve block to an adductor canal block would significantly reduce pain scores and opioid requirements compared to a group of patients that received only an adductor canal or femoral nerve block for medial patellofemoral ligament reconstruction in pediatric patients. The primary end-point is the number of patients achieving a Patient Acceptable Symptom State (PASS) (pain score less than four) for the entire 24-hour postoperative period in patients with and without a proximal sciatic block.Patients and Methods: This is a retrospective cohort study of 144 consecutive pediatric patients, ages 10 to 18 years, undergoing medial patellofemoral ligament reconstruction with peripheral nerve blockade for postoperative analgesia from 2016– 2020 at a pediatric orthopedics children’s hospital. Patients were divided into 2 cohorts with and without a proximal sciatic nerve block: group A/F: adductor canal or femoral CPNB and group AS: adductor canal CPNB and a proximal single-injection sciatic nerve block.Results: There was strong evidence for an increase in the number of patients who reported a pain score less than four for the entire 24-hour postoperative period in the group that received the additional proximal sciatic block. (PASS: A/F 13/62 (21%) vs AS 43/82 (52%), p< 0.001) There was strong evidence for a reduction in mean and maximum pain scores and opioid requirements in the first 24-hours after surgery in the proximal sciatic group.Conclusion: The addition of a proximal sciatic nerve block was associated with significantly reduced mean and maximum pain scores and opioid requirements after medial patellofemoral ligament reconstruction in pediatric patients and supports a randomized clinical trial to confirm these findings. Based on the results of this study we recommend the addition of a proximal sciatic nerve block, anterior or posterior, to an adductor canal block to provide improved analgesia and reduced opioid requirements in the 24-hours after MPFLR in pediatric patients.Keywords: adductor canal block, femoral nerve block, medial patellofemoral ligament reconstruction, sciatic nerve block, opioids